Artificial Neural Networks for Finite Capacity Scheduling: A Comparative Study - Guneri, Ali Fuat; Gumus, Alev Taskin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
In this study artificial neural networks are applied for finite capacity scheduling. Utilisation of artificial neural networks on solving finite scheduling problems is examined. Also a comparative model is proposed by using multi layer perceptron (MLP) neural networks and branch-and-bound algorithm, and carried out to solve a real world problem in a job shop scheduling system.